Pengaruh Motivasi Instrinsik, Pelatihan, Dan Kompensasi Finansial Terhadap Kinerja Individual Karyawan - Ananto, Dedi (LPPM Institut Bisnis dan Informatika Kesatuan, 2020)
AbstractThe purpose of this study was to examine the effect of Instrinsic Motivation, Training and financial compensation on individual employee performance. The method used was purposive sampling probability sampling with the sampling technique using Accidental Sampling. The sample in this study were 210 respondents. The data analysis method used is Multiple Linear Regression using SPSS version 24. The results of this study indicate that: Intrinsic motivation has a significant effect on individual employee performance as evidenced by the output where the t-count> t-table. Whereas for training and financial compensation it does not have a significant effect on individual employee performance, this is evidenced by the output where the t-count value is greater than the t-table.Keywords: intrinsic motivation; training; financial compensation